Peran Risiko Kredit Memoderasi Hubungan Efisiensi Operasional, Likuiditas Dan Kinerja Perbankan - Putu Pande R. Aprilyani Dewi; Ni Putu Budiadnyani; I Nyoman Sunarta; Putu Putri Prawitasari; Dhea Fitrisia (Universitas Medan Area, 2025)
Maximising banking performance involves optimising operational, financial, and risk management aspects. Operational efficiency, liquidity, and credit risk are key factors. This study is based on the theory of decision making and risk management. The research objective is to examine the effect of operational efficiency and liquidity on banking performance, as well as the moderating role of credit risk. The research was conducted on 223 BPR data in Denpasar (2020-2023). The novelty of the research lies in the context of BPR Denpasar and moderation analysis of credit risk. The results show that operational efficiency and liquidity affect banking performance. Meanwhile, credit risk moderates the relationship between operational efficiency and banking performance and credit risk does not moderate the relationship between liquidity and banking performance